Marketing of Sharia Halal Beach Tourism Through E-WOM - Armita Wahyu Ridho; Setyo Riyanto (JURNAL STUDI MANAJEMEN ORGANISASI, 2022)
At this time it is estimated that 207 million people embrace Islam. Of the 207 million inhabitants of the Muslim population 13% of the world's Muslims live in Indonesia and also implies that the majority of Indonesia's population adheres to the religion of Islam. Halal tourism is a tourism activity that is devoted to facilitating the Muslim travel needs. The term halal tourism emerged in 2015 when a World Halal Tourism Summit event was held in Abu Dhabi. Community activities in sharing their experiences through social media are Electronic Word of Mouth (e-WOM) activities. E-WOM activities usually use social media such as Instagram, Facebook, Path, Twitter, etc.Keywords: Marketing, Wisata Halal, E-WOM